Expanded Newborn Screening Program in Saudi Arabia: Incidence of screened disorders. (24th March 2017) - Alfadhel, Majid; Al Othaim, Ali; Al Saif, Saif; Al Mutairi, Fuad; Alsayed, Moeenaldeen; Rahbeeni, Zuhair; Alzaidan, Hamad; Alowain, Mohammed; Al‐Hassnan, Zuhair; Saeedi, Mohamad; Aljohery, Saeed; Alasmari, Ali; et al.
Abstract : Aim: To address the implementation of the National Newborn Screening Program (NBS) in Saudi Arabia and stratify the incidence of the screened disorders. Methods: A retrospective study conducted between 1 August 2005 and 31 December 2012, total of 775 000 newborns were screened from 139 hospitals distributed among all regions of Saudi Arabia. The NBS Program screens for 16 disorders from a selective list of inborn errors of metabolism (IEM) and endocrine disorders. Heel prick dry blood spot samples were obtained from all newborns for biochemical and immunoassay testing. Recall screening testing was performed for Initial positive results and confirmed by specific biochemical assays. Results: A total of 743 cases were identified giving an overall incidence of 1:1043. Frequently detected disorders nationwide were congenital hypothyroidism and congenital adrenal hyperplasia with an incidence of 1:7175 and 1:7908 correspondingly. The highest incidence among the IEM was propionic acidaemia with an incidence rate of 1:14 000. Conclusion: The article highlights the experience of the NBS Program in Saudi Arabia and providing data on specific regional incidences of all the screened disorders included in the programme; and showed that the incidence of these disorders is one of the highest reported so far world‐wide.